Nigel and the moon - Eady, Antwan (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2022)
When Nigel looks up at the moon, his future is bright. He imagines himself as...an astronaut, a dancer, a superhero, too! Among the stars, he twirls. With pride, his chest swells. And his eyes, they glow. Nigel is the most brilliant body in the sky. But it's Career Week at school, and Nigel can't find the courage to share his dreams. It's easy to whisper them to the moon, but not to his classmates--especially when he already feels out of place.